2007
DOI: 10.1097/sla.0b013e3180caa3c9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy in Aortoesophageal Fistulae

Abstract: The use of cryopreserved homografts is a valuable alternative to in situ repair with prosthetic vascular grafts or extra-anatomic reconstructions in the surgical treatment of AEF. Endovascular stentgraft placement plays a role as a bridging procedure in emergency situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…This treatment was found related to various complications, especially with graft contamination in the long term, while it seems effective, the minimally invasive and beneficial in the early period. However, it was indicated that this method can be applied in combination with the surgical treatment or act as a bridge until open surgery is applied ( 15 , 16 ). In a recent study reported by Akashi et al, it was indicated that aortic endovascular interventions alone is not a definitive method, and open surgical interventions such as aortic replacement through prosthesis or homograft, esophagectomy and repair with omentum are more effective in survival in the long term ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment was found related to various complications, especially with graft contamination in the long term, while it seems effective, the minimally invasive and beneficial in the early period. However, it was indicated that this method can be applied in combination with the surgical treatment or act as a bridge until open surgery is applied ( 15 , 16 ). In a recent study reported by Akashi et al, it was indicated that aortic endovascular interventions alone is not a definitive method, and open surgical interventions such as aortic replacement through prosthesis or homograft, esophagectomy and repair with omentum are more effective in survival in the long term ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the stent graft might be at risk of infection and subsequent recurrence of AEF because of the persistence of the esophageal opening; therefore, this approach may be considered a bridge to later definitive open surgical treatment with replacement of the thoracic aorta and simultaneous esophageal repair or resection. 14,15 In conclusion, an AEF can result from the natural progression of dissection of the descending thoracic aorta. Imaging studies after medical management are recommended for the surveillance of possible aneurysmal dilatation of the aorta.…”
Section: Discussionmentioning
confidence: 93%
“…The most frequent cause of primary AEF is thoracic aortic aneurysm, which is engendered by such causes as the rupture of penetrating aortic ulcer, foreign body swallowing, thoracic trauma, oesophageal cancer, and bronchogenic carcinoma. Secondary AEF, on the other hand, is frequently caused by surgical procedures done by graft because of aortic aneurysms or neighbouring organ surgeries [ 2 , 3 ]. Emergency surgical procedures to treat life-threatening massive bleeding following AEF have a high risk of mortality.…”
mentioning
confidence: 99%
“…In a review by Canaud et al [ 4 ], the authors reported 52.5% mortality rate in cases with AEF with sole use of TEVAR. Thus, many studies have recommended that TEVAR should be utilised as a bridge treatment to stabilise the patient prior to definitive treatment [ 2 , 4 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation